Review of generic limits of the tiger moth genera Virbia Walker and Holomelina Herrich-Schäffer (Lepidoptera: Arctiidae: Arctiinae) and their biogeography - Zaspel, Jennifer M.; Weller, Susan J. (Zootaxa, 2006)
A phylogeny for Holomelina and Virbia was constructed based on adult morphology. This study included 42 of the 70 recognized species in Holomelina and Virbia, two new species, and two elevated synonyms (H. marginata Druce and V. inversia Edwards). The following outgroups were chosen from the Arctiini: Arachnis picta Packard, Hypercompe permaculata Packard, Paracles fusca Walker, Phragmatobia fuliginosa (Linneaus), Pyrrarctia isabella (J. E. Smith), and Spilosoma virginica (Fabricius). Fifty-eight characters (195 states) were described and scored, including several newly discovered characters of the male and female abdomen and genitalia. Three male character systems, the shape and orientation of the basiphallus; the shape, orientation and ornamentation of the endophallus; and the pattern of sclerotization of the eighth male sternite, were important diagnostic characters for smaller clades and species. The maximum parsimony analysis of all taxa with 100 randomized repetitions yielded 779 trees with a length (L) of 1698, a consistency index (CI) of 0.41 and a retention index (RI) of 0.65. Holomelina species were placed in two clades, an H. aurantiaca clade and an H. opella clade that was paraphyletic with respect to Virbia. The ingroup clade comprised of Holomelina and Virbia species was supported by eleven synapomorphies and a Bremer index higher than fifteen. The decay of this node was greater than 10. Taxon jack-knife analyses revealed that results were sensitive to the inclusion of two outgroup species, A. picta and P. fuliginosa. When either was removed the relationships of ingroup taxa became unresolved. When the analysis was restricted to species which represented by both males and females, we recovered an ingroup consisting of Holomelina and Virbia species, but the strict consensus of 123 trees (L = 1356, CI = 0.47, RI = 0.65) resulted in a polytomy of smaller clades. Neither analysis recovered a reciprocally monophyletic Holomelina and Virbia. We place Holomelina as a junior generic synonym of Virbia and provide a species checklist for Virbia. Biogeographic areas were scored from distribution information in a specimen-level database consisting of over 12,000 specimens. The following eight areas were recognized: A. western USA and Canada, B. central USA and Canada, C. eastern USA and Canada, D. southwestern USA and Mexico, E. central America, F. western South America, G. eastern and central South America, and H. highlands of northern South America. A weighted ancestral area analysis was used to determine ancestral areas for five major ingroup clades. We propose replacing the name “probability index” (PI) of Bremer with the term “Weighted Area Index (WAI)” because the PI of Bremer is not based on a statistical distribution and the term is misleading We determined that the ancestral area for Virbia was most likely the southwestern United States and Mexico. The species distributed in North America north of Mexico represent a composite fauna with a minimum of two dispersal events from Mexico into the northern latitudes. In contrast, the South American fauna appears to have a single origin.